Self-assembled optical diffraction sensor for water quality monitoring : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering, Massey University, Albany, New Zealand - Jaywant, Swapna (Massey University, 2020)
Water contamination is one of the current global issues; the freshwater sources being extremely restricted are causing a drinking water crisis in many countries. An increase in water contamination continuously decreases water quality. Generally, water pollution includes pathogenic, nutrients, and chemical (organic & inorganic) contaminants. Inorganic contamination involves metallic particles such as arsenic, lead, etc. Of these contaminants, arsenic (As) is a major concern due to its mutagenic and carcinogenic effects on human health. The World Health Organisation has recommended the maximum contamination limit (MCL) for arsenic in drinking water to be 10 µg/L. Countries like Bangladesh, China, Vietnam, India, Chile, USA, and Canada are contaminated with arsenic. Arsenic species are also found in New Zealand in 28 geothermal features from the Taupo Volcanic Zone and the Waikato region. Thus, a rising level of arsenic in drinking water creates the need to periodically monitor its levels in potable water. Commercially available methods are either laboratory-based or kit based techniques. The most common laboratory-based arsenic detection methods are reliable. However, these are expensive due to the requirement for specific instrumentation. Hence, they are not considered to be field-effective for arsenic detection. On the other hand, commercially available kit-based methods are portable but are not considered to be safe and reliable due to the production of toxic by-products. The development of a portable and sensitive arsenic sensor with high throughput could be an asset. In this research, we present a novel sensor with a unique surface modification technique to detect arsenite (As(III)) contamination of water. Here, the approach involves the potential usage of self-assembled optical diffraction patterns of a thiol compound (dithiothreitol or glutathione) on the gold-coated glass. The self-assembled patterns are obtained through a microcontact printing (µCP) procedure. Gold binds with the thiol compound through an Au-S linkage. In addition to this, As(III) has an affinity towards amino acids, amines, peptides, and organic micro molecules due to As-O or As-S linkages. The research indicates that the total time taken by the µCP process to transfer the patterns successfully on to the gold-coated substrate is inversely proportional to the concentration of the thiol molecules and pH value of the solvent. Further, the signal enhancement of these thiol-based self-assembled patterns allows for detection of the As(III) contamination. Simultaneously, the automated fluidic system is designed to provide fluid handling. The system is developed with the help of off-the-shelf and/or in-house fabricated components. The characterisation of fluidic components proved that the low-cost fluidic components work reliably in the fluidic network and can be used in sensing applications for pumping, mixing, and circulation purposes. We also explore the possibility of using fused deposition modelling and selective laser sintering technology for the printing of the flow chamber through printing microchannels. These two technologies have been compared in terms of the minimum possible channel size, fluid ow-rate, and leakage. Overall, we developed a sensing scheme of a portable self-assembled diffraction sensor for As(III) detection. The developed sensor can detect dissolved As(III) up to 20 µg/L. The µCP of a dithiothreitol pattern has not been found in the literature yet. Hence, this research also provides a guide towards µCP of dithiothreitol on a gold-coated substrate.
Figures are re-used with permission, or under a Creative Commons Attribution license.
Keywords: Water quality; Measurement; Equipment and supplies; Optical detectors; Design and construction; Drinking water; Arsenic content; 400411 Water treatment processes